MINI EDU-FARM AS AN EDUCATIONAL FACILITY FOR GOAT/SHEEP FARMERS THAT IS INTEGRATED WITH TOURISM OF EMBUNG PENDEM MAGETAN - Sunaryo Hadi Warsito; Mirni Lamid; Nanik Hidayatik; Herry Agoes Hermadi; Irham Zaki (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Pendem Village, Ngariboyo District, Magetan Regency is one of the villages that has a potential tourist attraction, namely Embung Pendem. The Embung Pendem functions as a water source to irrigate rice fields in three villages, namely Banyudono and Pendem Villages in Ngariboyo District and Joketro Village in Parang District. Mini Edu-Farm for goat/sheep farming aims to provide education about raising goats/sheep properly to the community, especially goat/sheep farmers in Pendem Village. Increase public interest and knowledge about goat/sheep farming. The method used in implementing this Community Service activity is carried out in two activity stages, including the counseling/development stage and cage repair. The results of Community Service include an increase in farmers' knowledge about how to properly care for goats/sheep, handling reproductive disorders and farmers' knowledge of goat/sheep farming products and their business potential as well as the existence of a stilt model pen with a collection system as a model pen. In conclusions, the outreach activities conducted as part of Community Service  have improved the knowledge regarding the goat/sheep husbandry, reproductive health and their economic potential. Furthermore \, sustained collaboration between universities and the community, especially livestock farmers, is essential to enhance their knowledge and insight, so that existing theories can be effectively implemented by farmers as direct practitioners.